Chip-scale atomic diffractive optical elements - Liron Stern (Nature Portfolio, 2019)
Quantum coherence and the nonlinear properties of atoms are highly useful in optical devices. Here the authors show quantum-optic hybrid platforms in fully integrated chip-scale atomic diffractive optical elements by embedding hot atomic Rb vapor in microfabricated structures in silicon.